Integrating Islamic Counseling and Guidance (BK Islami) Curriculum into Madrasah Aliyah Management System: Problem or Solution? - Faiz Musthofa Abbas; Sapari Sapari; Yusuf MZ (Lentera Peradaban: Journal on Islamic Studies, 2025)
The discourse on integrating Islamic values into Guidance and Counseling (BK) services at Madrasah Aliyah often encounters a structural dilemma: the transcendental vision is not accompanied by an adequate managerial system. The Islamic BK curriculum is adopted normatively, but it often remains symbolic and detached from the institution's policy architecture. This study aims to examine how the madrasah management system internalizes Islamic values into the planning, implementation, and evaluation of BK services. The research uses a qualitative approach with a single case study design at an Islamic-based Madrasah Aliyah. Data collection techniques include in-depth interviews, participatory observation, and institutional document analysis. The results show that the integration of the Islamic BK curriculum is partial and lacks a systemic managerial strategy. The dominance of an administrative approach, weak leadership roles, and the absence of a value-based evaluation mechanism are the main factors hindering the internalization of Islamic values in BK services. This study recommends a reformulation of Islamic educational management policies that position BK services as a transformative, rather than merely procedural, instrument.